2006
DOI: 10.1007/s00167-006-0079-9
|View full text |Cite
|
Sign up to set email alerts
|

Pullout strength of meniscal repair after cyclic loading: comparison of vertical, horizontal, and oblique suture techniques

Abstract: This in vitro biomechanical study with cyclic loading compared the pullout strength of vertical, horizontal, and oblique sutures used for meniscal lesion repair. Following repair of vertical longitudinal lesions created in bovine medial menisci, three groups of seven specimens (vertical, horizontal, and oblique sutures) underwent cyclic loading in a randomized test order (5 mm/min, cycling between 5 and 50 N at 1 Hz for 100 cycles) prior to load to failure testing (5 mm/min). Displacement did not differ betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 18 publications
0
37
0
2
Order By: Relevance
“…Therefore, this should provide the most pertinent information regarding the biomechanical properties. We used a single vertical suture because it is well known that the strength of the vertical loop suture is superior to that of the horizontal suture due to the perpendicular orientation of the meniscal fibers relative to the repair device [21]. …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this should provide the most pertinent information regarding the biomechanical properties. We used a single vertical suture because it is well known that the strength of the vertical loop suture is superior to that of the horizontal suture due to the perpendicular orientation of the meniscal fibers relative to the repair device [21]. …”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, some oblique or cross-suture methods have been applied in the treatment of radial tears of the meniscus and have achieved good results [30][31][32] . Biomechanical studies have shown [33] that oblique sutures have the dual advantage of vertical sutures (superior biomechanical strength) and horizontal sutures (ease of application, longer sutures with a tendency to cover a larger meniscal tissue area). According to such theoretical and practical results, we hypothesize that if it is applied to the remediation of unilateral suture anchor pulling out of an all-inside meniscal repair system, the clinical efficacy of this method may be improved.…”
Section: Discussionmentioning
confidence: 99%
“…Several in vitro animal and human studies have shown that the vertical and oblique suture repairs have superior load to failure compared with horizontal repair. [37][38][39][40] Until further mechanical studies are performed on meniscal suture techniques in dog menisci we would recommend a vertical or cruciate suture repair.…”
Section: Discussionmentioning
confidence: 99%